Behavioral Economics and Health Decision-Making: A Study on Preventive Health Behavior in Urban Communities - Pratiwi Indariani; Achmad Fauzan Mahfuds (Generasi Sains Indonesia, 2025)
Preventive health practices play a vital role in reducing the risks of chronic diseases and enhancing population well-being. Despite this, preventive measures such as immunization, regular check-ups, balanced diets, and exercise remain underutilized in metropolitan areas. This study adopts a behavioral economics perspective to examine how cognitive biases shape urban residents’ decisions regarding preventive health behaviors. A quantitative survey was conducted among 392 respondents across diverse socioeconomic backgrounds, focusing on present bias, status-quo bias, and bounded rationality. The results revealed significant negative correlations between these biases and preventive health practices. Specifically, present bias strongly predicted delays in medical check-ups, status-quo bias hindered the adoption of healthier routines, and bounded rationality contributed to the misinterpretation of health-related information. Socioeconomic status further moderated these outcomes, with higher-income individuals more likely to engage in preventive measures. The findings underscore the importance of applying behavioral insights such as framing effects, default options, and simplified health communication to improve uptake of preventive practices in urban environments. Policymakers are urged to integrate behavioral nudges with equity-oriented health initiatives to address persistent disparities.